ANALYSIS OF STUNTING INCIDENCE IN TODDLERS AT MUARA ENIM HEALTH CENTER - Oktavia, Risnia; Arie Wahyudi; Lilis Suryani (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Stunting is a condition where a child's physical development is impaired, resulting in a shorter stature than appropriate for their age. This study aims to determine the factors associated with stunting among children under five at Muara Enim Public Health Center, Muara Enim District, in 2025. This research employed a quantitative design with a case-control approach. The population consisted of mothers with stunted children in 2024. The sample included both case and control groups with a 1:1 ratio. The case group consisted of 30 children under five with stunting in 2024, while the control group included 30 non-stunted children from the Muara Enim Public Health Center area, totaling 60 respondents. The sampling technique used total sampling for the case group and simple random sampling for the control group. The research was conducted from May 2 to May 16, 2025. Data were collected using questionnaires. Bivariate data analysis was conducted using the Chi-Square test, and multivariate analysis was also performed. The results showed significant associations between stunting and the following variables: maternal age (p-value 0.00), maternal education (p-value 0.00), family income (p-value 0.00), birth weight (p-value 0.00), birth spacing (p-value 0.00), history of infectious disease (p-value 0.00), exclusive breastfeeding (p-value 0.00), clean water source (p-value 0.00), and feeding practices (p-value 0.00). The most dominant factor associated with stunting was the clean water source (p-value 0.00; OR: 25.0). The health center is advised to improve access to clean water and provide sanitation education to the community, particularly to families with children under five, deliver nutrition education to mothers of young children, and conduct screening for children at risk of stunting